TRANS MODEL MATHEMATICS EDUCATION (T2ME) UNTUK MENINGKATKAN KETERAMPILAN OPERASI HITUNG PERKALIAN BERBANTUAN TEKNIK SUBATSAGA DI SEKOLAH DASAR - Oktafiani, Wilda; Budiarti, Miladi Rizkyah; Solekha, Solekha; Yulistia, Tia Fuja; Oktaviani, Oriza Mutia; Widodo, Suprih (Universitas Pendidikan Indonesia, 2018)
This research is conducted to produce a product that can organize learning well and can ease problem solving in learning especially mathematics. The resulting product is the development of learning models and create an easy techniques as a solution to complete multiplication in Elementary School (SD). This is motivated by the low ability to solve various multiplication problem that occurred in the 4th grade in Elementary School (SD). This data was obtained based on observation and interviews conducted with teacherâ€™s classroom at some public Elementary Schools in Purwakarta district. In one of the public Elementary Schools it was found that only 25% of students were able control multiplication. Based on the problems, the research method use is Research and Development (RD) Borg and Gall. Product design that will be developed and applied that is model of learning model of mathematics education model (T2ME) and technique of SuBatSaGa multiplication. Our Product design developed has been approved by the experts. The experts in this research that is lecturer of mathematics.Â Keywords: multiplication, Trans Model Mathematics Education (T2ME), SuBatSaGa technique.